2014
DOI: 10.1021/ja507147p
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Silicon-Based Layered Structures for Optoelectronic Applications

Abstract: A method based on the particle swarm optimization (PSO) algorithm is presented to design quasi-two-dimensional (Q2D) materials. With this development, various single-layer and bi-layer materials in C, Si, Ge, Sn, and Pb were predicted. A new Si bi-layer structure is found to have a much-favored energy than the previously widely accepted configuration. Both single-layer and bi-layer Si materials have small band gaps, limiting their usages in optoelectronic applications. Hydrogenation has therefore been used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 49 publications
(84 reference statements)
2
65
0
Order By: Relevance
“…By performing global structure optimization [44], we find that the buckled Hg3As2 structure [as shown in Hamiltonian is derived to understand the effect of buckling on the electronic structure (see supplementary material). We find an additional third-order term of k due to the buckling, which explains why the band gap is opened along  → M , but the gap is tiny.…”
Section: D Nls In the Hk Latticementioning
confidence: 99%
“…By performing global structure optimization [44], we find that the buckled Hg3As2 structure [as shown in Hamiltonian is derived to understand the effect of buckling on the electronic structure (see supplementary material). We find an additional third-order term of k due to the buckling, which explains why the band gap is opened along  → M , but the gap is tiny.…”
Section: D Nls In the Hk Latticementioning
confidence: 99%
“…Based on the ab initio structure and phonon‐mode calculations, several 2D silicon allotropes related to silicene and dumbbell units have been proposed, such as large honeycomb dumbbell silicene (LHDS) , trigonal dumbbell silicene (TDS) , honeycomb dumbbell silicene (HDS) , and similar allotropes have also been proposed for other IV‐group materials . In addition, it is found that MoS 2 ‐like silicene, Si‐Cmme , siliconeet and double‐layer silicene are more stable than pristine silicene. These studies indicate the possibility of finding new stable 2D Si allotropes.…”
Section: Introductionmentioning
confidence: 83%
“…These progresses provide potential material candidates for solving energy crisis and environmental problems. For example, 2D semiconductors with proper bandgaps, excellent sunlight absorption ability, and charge‐transfer efficiency can be used to convert solar energy to electrical energy . Also, those with further suitable band‐edge positions are highly expected for sunlight‐driven water‐splitting as efficient photocatalyst due to their high surface ratio.…”
Section: Calculated Lattice Parameters Space Group Layer Thicknessmentioning
confidence: 99%